Comic book collections and programming a practical guide for librarians - Wood, Matthew Z. (Practical guides for librarians, 2018)
"Comic Book Collections and Programming will help librarians build a collection that's right for their library, including specialty collections for kids, teens, and adults. It covers the practical realities of this non-traditional format, like binding, weeding, and budgeting. It also address advanced topics like comics and pedagogy, bringing comics artists and authors into the library, and using comics as a community outreach tool, even hosting comic conventions in libraries" --Provided by publisher.